Preclinical assessment of the receptor-binding domain of Plasmodium vivax Duffy-binding protein as a vaccine candidate in rhesus macaques - Moreno, A. (2008)
The receptor-binding domain of Plasmodium vivax Duffy binding protein, region II (PvRII), is an attractive candidate for a vaccine against P. vivax malaria. Here, we have studied the safety and immunogenicity of recombinant PvRII in Macaca mulatta (rhesus monkeys). Recombinant PvRII with a C-terminal 6-histidine tag was expressed in E. coli, recovered from inclusion bodies, refolded into its functional conformation, purified to homogeneity and formulated with three adjuvants, namely, Alhydrogel, Montanide ISA 720 and the GSK proprietary Adjuvant System AS02A for use in immunogenicity studies. All the PvRII vaccine formulations tested were safe and highly immunogenic. The overall magnitude of the antibody response was significantly higher for both Montanide ISA 720 and AS02A formulations in comparison with Alhydrogel. Furthermore, there was a significant correlation between antibody recognition titers by ELISA and binding inhibition titers in in vitro binding assays. The PvRII vaccine formulations also induced IFN-γ recall responses that were identified using ex vivo ELISPOT assays. These results provide support for further clinical development of a vaccine for P. vivax malaria based on recombinant PvRII.